Knockdown of eIF3a ameliorates cardiac fibrosis by inhibiting the TGF-Î²1/Smad3 signaling pathway - Li, B; Chen, H; Yang, X; Wang, Y; Qin, L; Chu, Y (Cellular and Molecular Biology, 2016)
Cardiac fibroblasts are key effector cells in the pathogenesis of cardiac fibrosis. The eukaryotic translation initiation factor (eIF) 3a is the largest subunit of the eIF3 complex and has been involved in renal fibrosis. However, the precise role of eIF3a in myofibroblast differentiation and cardiac fibrosis remains unknown. Accordingly, in our present study, we tested the expression of eIF3a in transforming growth factor Î²1 (TGF-Î²1)-induced rat CFs and found that eIF3a was upregulated in TGF-Î²1-induced rat CFs. Then the role and mechanism of eIF3a in cardiac fibrosis were explored. Our results found that the eIF3a expression was significantly up-regulated in TGF-Î²1-induced CFs. Knockdown of eIF3a significantly inhibited TGF-Î²1-induced CF proliferation, as well as suppressed the expression levels of Î±-smooth muscle actin (Î±-SMA) and SM22Î±. Mechanistically, knockdown of eIF3a attenuated TGF-Î²1-induced Smad3 activation in CFs. In summary, our present study firstly demonstrated that silencing eIF3a might alleviate TGF-Î²1-induced cardiac fibrogenesis in CFs by inhibiting Smad3 activation, and suggest that eIF3a may be positioned as a new and promising target for the prevention and treatment of cardiac fibrosis.